Decolorization of Remazol Black B Solution by PbO2 Modified Fenton Method in a Scaled Up Reactor - Muhamad Abduh Hasibuan; Didik Setiyo Widodo; Retno Ariadi Lusiana (Jurnal Kimia Sains dan Aplikasi, 2018)
Study on decolourization of remazol black B (RBB) solution has been performed in a scale up reactor. As an artificial waste, the dye sample that contains azo groups is difficult to decompose under ordinary environmental conditions so it requires further treatment before discharging to open aquatic system. Many efforts have been reported and further developed toward other azo dyes. One of an outstanding approach is Fenton method. This study modified the method with PbO2 rather than Fe2+. In this modification, the dyestuff was degraded by radical •OH resulting from reaction between H2O2 and Pb2+ ion generated from PbO2. In Preliminary works, decolourization was performed and optimized in lab-scaled. Analysis were conducted and the best condition was applied to decolorize the sample in a scale-up size. Characteristics of the reactor was also determined. Results showed that at optimum condition, 100 mL of 50 ppm remazol black B was decolorized up to 98.82 % within 15 minutes. On scale up to 1 L-sized reactor, within the time highest percentages of remazol black B decolourization was reached 82.02 % by addition of 10 % H2O2 and COD decrease to 98.96 %. In the 1 L reactor, RBB sample with concentration of 50 ppm, PbO2 1 gram and H2O2 10 % obey the proposed decolourization equation of D = -0,0011x2 + 0.5705x – 0.6788 with x = volume peroxide (in mL), D = percent of decolourization.